(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
It is being main aim to reduce the usage of chemical substances for plant protection, in Mongolian agricultural sector, by isolating and of course determining local strain that can fit in condition of our country specifically to control harmful pests that are having negative impact on the environment especially in the forest and pasture plants. Thus, research work concentrated on isolating bioproduct based on local strain of entomopathogenic fungi Metarhizium anisopliae and to determine its biological activity. Bioproduct of Ma.Mn-G09/22local strain have been experimented with 3 variants with 3 repetitions and comparing it with control in Munh-Khairhan sum of Tuv aimag. Our study involved open field and vivarium experiment which both showing similar results, providing local strain G0922 of Metarhizium anisopliae fungi can be effective against harmful grasshopper Eclipophleps bogdanovi sergtarb under field conditions. Journal of agricultural sciences №15 (02): 147-151, 2015